2019
DOI: 10.33233/eb.v18i3.2642
|View full text |Cite
|
Sign up to set email alerts
|

Idosos institucionalizados e depressão: rastreamento dos sintomas

Abstract: Introdução: No Brasil, com a transição demográfica, o número de pessoas que alcançam a terceira idade tem aumentado significativamente e, paralelamente a esse processo, observa-se um aumento gradativo de perturbações de humor nessa etapa da vida, principalmente o transtorno depressivo. Objetivo: Analisar a prevalência de sintomas depressivos em idosos institucionalizados. Métodos: Estudo descritivo, com abordagem quantitativa, desenvolvido com idosos de três instituições de longa permanência no município de Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…19 Regarding the factors related to the nursing diagnosis studied, it is important to emphasize that loneliness as well as anxiety, influence variations in the mood of elderly people, causing depression. 5 It should be noted that other factors such as changes in the sleep pattern and social isolation were also expressed by the elderly. Research has found that in addition to mood swings, depressive symptoms are directly associated with poor quality and sleep disorders and may influence the health and quality of life of institutionalized elderly people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Regarding the factors related to the nursing diagnosis studied, it is important to emphasize that loneliness as well as anxiety, influence variations in the mood of elderly people, causing depression. 5 It should be noted that other factors such as changes in the sleep pattern and social isolation were also expressed by the elderly. Research has found that in addition to mood swings, depressive symptoms are directly associated with poor quality and sleep disorders and may influence the health and quality of life of institutionalized elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…20 In the context of ILPIs, social isolation is generally associated with the absence of visits from relatives, solitude or widowhood, since interpersonal relationships corroborate quality of life and maintenance of psychic health. 5 From this point of view, the literature also emphasizes the risk of suicidal behavior linked to the institutionalization process, considering aspects such as the loss of affective ties, the occurrence of chronic diseases, loneliness, hopelessness and lack of meaning for life. 21 For many, facing old age, particularly in the context of institutionalization, means being vulnerable to all the aforementioned factors, which may induce a depression picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para mapear os principais achados dos estudos incluídos nesta revisão integrativa, avançou-se para discussão dos achados. A maioria dos estudos contemplou as implicações sociais (CALDERÓN, 2018;FERRAIUOLI;FERREIRA, 2018;RODRIGUEZ et al, 2018;ROSSETTI et al, 2018;SAINTRAIN et al, 2018;SOUZA JÚNIOR et al, 2018;ARAVENA;GAJARDO;SAGUEZ, 2019;FRUTUOSO et al, 2019;GUIMARÃES et al 2019;NASCIMENTO;BASTITONI, 2019;PUELLO et al, 2019;QUINTANA et al, 2019;RAMOS et al, 2019;SANTOS, 2019;SILVA et al, 2019).…”
Section: Discussionunclassified
“…Guimarães et al (2019) acrescentam que há alta prevalência de sintomas depressivos em idosos institucionalizado. Diante disso, Frutuoso et al (2019) defendem que seja primordial a criação de programas para idosos institucionalizados, e que tais programas visem a promoção social, cultural, de lazer, de esporte e educacional.…”
Section: Discussionunclassified